2014
DOI: 10.1007/s13595-014-0368-2
|View full text |Cite
|
Sign up to set email alerts
|

Optimal seed water content and storage temperature for preservation of Populus nigra L. germplasm

Abstract: ) is an alluvial forest tree species whose genetic pool is decreasing in Europe. Poplar trees produce short-lived seeds that do not store well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 12 publications
0
30
0
1
Order By: Relevance
“…Seeds were stored in closed plastic vials at four different temperatures (3°C, −3°C, −10°C, −20°C) or cryostored at −196°C in liquid nitrogen (LN) for 24 months. Chosen temperatures are recommended for shortterm (3°C, −3°C) (Tylkowski 2010; Suszka et al 2014) or long-term (−10°C, −20°C, −196°C) (Sato 1955;Stanton and Villar 1996; Tylkowski 2010) storage for poplar seeds. Additionally, fresh seeds that were collected in 2012 were used as a control.…”
Section: Plant Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seeds were stored in closed plastic vials at four different temperatures (3°C, −3°C, −10°C, −20°C) or cryostored at −196°C in liquid nitrogen (LN) for 24 months. Chosen temperatures are recommended for shortterm (3°C, −3°C) (Tylkowski 2010; Suszka et al 2014) or long-term (−10°C, −20°C, −196°C) (Sato 1955;Stanton and Villar 1996; Tylkowski 2010) storage for poplar seeds. Additionally, fresh seeds that were collected in 2012 were used as a control.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Additionally, fresh seeds that were collected in 2012 were used as a control. Details of the storage protocols were described in Suszka et al (2014) and Michalak et al (2014).…”
Section: Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Survival and regeneration was better noticed either on the embryonic axes that were chopped off and dehydrated prior cryopreservation treatment or from the embryonic axes extracted from already cryopreserved seeds. Suszka et al (2014) reported that both fresh and desiccated seeds of Populus nigra could be preserved using standard cryopreservation techniques for about two years.…”
Section: Influence Of Moisture Contentmentioning
confidence: 99%
“…Gantait et al (2015), on the other hand, unloaded the sample in 1.2 M sucrose after quick thawing and then relocated onto double layered sterile filter paper kept on Petri dishes enclosing semi-solid MS medium with 3% (w/v) sucrose and 100 mg l -1 myoinositol devoid of any plant growth regulators. The samples were given dark phase for consecutive 7 days before disclosure to light with a 16 h photoperiod at 26±2 o C. Suszka et al (2014) germinated the desiccated seeds in a Jacobsen germinator. Moist filter paper was used to rehydrate the seeds and cool white light was supplied on a 12 h cycle.…”
Section: Post-cryopreservation Regrowthmentioning
confidence: 99%